The Relationship Between Personality Types and Attitudes Toward Psychiatry Among Medical and Psychology Students in the United Arab Emirates: A Cross-Sectional Study - Syed Fahad Javaid; Jigna Stott; Gabriel Andrade; Nusrat Khan (BJPsych Open)
Aims: While personality traits are known to influence values, beliefs, and professional preferences, limited research has explored their impact on attitudes toward psychiatry, particularly in Middle Eastern contexts and among non-medical students. Personality traits also influence perceptions of mental illness among individuals, helping to understand the basis of societal mental health stigma. Understanding the relationship between personality traits and attitudes toward psychiatry is crucial for developing educational strategies that support positive perceptions, ultimately enhancing healthcare outcomes for individuals living with mental illnesses.